Melatonin Expresses Powerful Anti-inflammatory and Antioxidant Activities Resulting in Complete Improvement of Acetic-Acid-Induced Colitis in Rats - (:unkn) unknown (SPRINGER, 2011)
Increased free-radical production, decreased antioxidant capacity, and excessive inflammation are well-known features in the pathogenesis of inflammatory bowel disease. Melatonin is a powerful antioxidant and a scavenger of hydroxyl radicals. Melatonin has also been shown to have anti-inflammatory activities in tissues. Our study objective is to investigate the effects of melatonin on tissue inflammatory activities using an ulcerative colitis (UC) model induced by acetic acid (AA) in rats. Wistar rats (n = 32) were divided into four groups. AA-induced colitis was performed in two of the groups, while the other two groups were injected with saline intrarectally. One of the AA-induced colitis groups and one of the control groups were administered 100 mg/kg/day melatonin intraperitoneally, and the pair groups were given saline. After 4 days, colonic changes were evaluated biochemically by measuring proinflammatory cytokines [tumor necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, and IL-6], myeloperoxidase (MPO), malondialdehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD) levels in tissue homogenates and by histopathological examination. AA caused colonic mucosal injury, whereas melatonin suppressed these changes in the AA-induced colitis group (P < 0.001). AA administration resulted in increased TNF-alpha, IL-1 beta, IL-6, MPO, and MDA levels, and decreased GSH and SOD levels, whereas melatonin administration reversed these effects (all P < 0.001). The present study proposes that melatonin has a dual action as an effective anti-inflammatory and an antioxidant, and may be a hopeful therapeutic agent for UC.
Keywords: Melatonin; Ulcerative colitis; Inflammatory bowel disease; Oxidative stress; Tumor necrosis factor; Cytokine; INFLAMMATORY-BOWEL-DISEASE; ULCERATIVE-COLITIS; BLOOD-PLASMA; VITAMIN-E; INJURY; DEFENSES; COLON; ASSAY; SHOCK